1989
DOI: 10.1177/019459988910000607
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA Aneuploidy with Human Papillomavirus‐Induced Malignant Transformation of Sinonasal Transitional Papillomas

Abstract: The nuclear DNA content of 19 transitional papillomas of the sinonasal region and 9 maxillary squamous cell carcinomas was studied by flow cytometry; the presence of human papillomavirus (HPV) DNA types 11 and 16 was determined by the in situ hybridization technique from paraffin-embedded tissue. Thirteen (68%) of the papillomas and none of the carcinomas contained HPV genome. Six (32%) of the papillomas and 4 (44%) of the carcinomas had an aneuploid DNA content. The relative DNA content (DNA index) of the ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Although all the 12 nasal papillomas examined in this study had no evidence of cancerous change, the tendency for malignant transformation of nasal papillomas [ 11, and especially nasal papillomas with HPV 16 DNA [7], has been reported. Therefore, careful follow-up of patients with nasal papillomas containing HPV 16 DNA would seem to be important.…”
Section: Detection Of Hpv Dna By Southern Blot Hybridisationmentioning
confidence: 70%
See 3 more Smart Citations
“…Although all the 12 nasal papillomas examined in this study had no evidence of cancerous change, the tendency for malignant transformation of nasal papillomas [ 11, and especially nasal papillomas with HPV 16 DNA [7], has been reported. Therefore, careful follow-up of patients with nasal papillomas containing HPV 16 DNA would seem to be important.…”
Section: Detection Of Hpv Dna By Southern Blot Hybridisationmentioning
confidence: 70%
“…Among them, all of seven recurrent cases contained HPV DNA. Klemi et al [7] also reported that all four cases of recurrent sinonasal papillomas yielded HPV DNA types 11/16, and Fu et al [12] reported all three recurrent fungiform nasal papillomas studied had HPV DNA types 6/11. Conversely, HPV was not detected in normal nasal mucosa [13].…”
Section: Detection Of Hpv Dna By Southern Blot Hybridisationmentioning
confidence: 95%
See 2 more Smart Citations
“…There is some evidence, however, to suggest that HPV 16 and 18 may be more carcinogenic than HPV 6 and 11 (45,46,49). In the studies of Klemi et al (45) (32%) were aneuploid, and of the 6 that were aneuploid, 2 (33%) were associated with carcinomas.…”
Section: Carcinoma and Ipmentioning
confidence: 99%